Technical Feasibility of Integrated Laboratory in Faculty of Sports Science Universitas Negeri Semarang - Setiawan, Ipang; Abdulaziz, Moch Fahmi; Dharmawan, Dhimas Bagus (Universitas Negeri Semarang, 2017)
This research aims to analyze the requirements of technical integrated laboratory FIK Unnes in improving sports achievement in Central Java Province, Indonesia. Research method used in this research was qualitative descriptive, with evaluation approach, the instrument used document analysis, observation, interview and inquiry. Data analysis used by using Miles and Huberman interactive cycle then the pattern tendency was explained, qualitative analysis was initiated by describing reality happened in narration form then it was interpreted by a guidebook with ISO 17025 or SNI 17025 standard in laboratory. The result shows that the requirements of technical integrated laboratory FIK Unnes was quite maximum to contribute in improving sports achievement in Central Java Province, Indonesia, it was based on the technical standard from equipment, personnel, accommodation and environment condition, finding of test and measurement, quality assurance of measurement and test result, and reporting of result conducted based on ISO 17025 or SNI 17025 standard.